The Role of E3, E4 Ubiquitin Ligase (UBE4B) in Human Pathologies - Antoniou, Nikolaos (Cancers (Basel), 2019)
The genome is exposed daily to many deleterious factors. Ubiquitination is a mechanism that regulates several crucial cellular functions, allowing cells to react upon various stimuli in order to preserve their homeostasis. Ubiquitin ligases act as specific regulators and actively participate among others in the DNA damage response (DDR) network. UBE4B is a newly identified member of E3 ubiquitin ligases that appears to be overexpressed in several human neoplasms. The aim of this review is to provide insights into the role of UBE4B ubiquitin ligase in DDR and its association with p53 expression, shedding light particularly on the molecular mechanisms of carcinogenesis.